Cetyltrimethylammonium bromide‐coated agrosorbents and their high benzene adsorption performance from aqueous solution. Issue 1 (6th July 2017) - Kong, Helen; Cheu, Siew Chin; Othman, Nurul Sakinah; Song, Shiow Tien; Johari, Khairiraihanna; Saman, Norasikin; Lye, Jimmy Wei Ping; Mat, Hanapi
Abstract : Cetyltrimethylammonium bromide‐coated agrosorbents were successfully synthesized through firstly mercerization of raw banana trunk (Raw‐BT) with alkali (M‐BT) and finally coating with cetyltrimethylammonium bromide (M‐CTAB‐BT). The characterization was done using an energy dispersive X‐ray spectrophotometer, a Fourier transform infrared spectrophotometer and a field emission scanning electron microscope. The Brunauer, Emmett, and Teller analysis was also conducted. The benzene adsorption performance of BT agrosorbents was improved by mercerization and surfactant coating according to the following order: Raw‐BT (340.25 × 10 −  mmol/g) < CTAB‐BT (382.41 × 10 −3  mmol/g) < M‐CTAB‐BT (535.62 × 10 −3  mmol/g). The adsorption data obeyed the Langmuir and pseudo‐second order (PSO) kinetic models with film diffusion as the rate‐limiting step. The agrosorbent regeneration as well as comparison to literature data indicated the modified BT and thus the agrowaste biomass could be alternative agrosorbent precursors for removing benzene from aqueous solutions. © 2017 American Institute of Chemical Engineers Environ Prog, 37: 305–317, 2018